Current Perspectives of convalescent plasma therapy in COVID-19 - Sahu, Kamal Kant; Mishra, Ajay Kumar; Raturi, Manish; Lal, Amos (Acta Biomedica Atenei Parmensis, 2020)
The outbreak of the coronavirus disease 2019 (COVID‐19) has posed an unprecedented challenge to the health care communities across the globe. As of June 2, 2020, a total of 6,418,968 confirmed COVID-19 cases with 378,954 deaths have been reported. Different regions of the world have reported varying intensity of COVID-19 severity. The disease burden for COVID-19 depends on multiple factors like the local infection rate, susceptible population, mortality rate, and so on. The COVID-19 pandemic is a rapidly evolving emergency and is a subject of regular debate and advanced research. As of today, there is a lack of definitive treatment options for COVID-19 pneumonia. In search of alternative options, few drugs are being tested for their efficacy and repurposing. Preliminary reports have shown positive outcomes with Remdesivir and tocilizumab, but this needs further confirmation. Recently, the therapeutic application of Convalescent Plasma therapy in critically ill patients suffering from COVID-19 has gained momentum. We hereby discuss the convalescent plasma as a potential therapeutic option, its challenges of finding the ideal donors, transfusion medicine responsibilities, and the current global experience with its use.